(untitled) (Bangladesh Journal of Neurosurgery, 2022)
Background: The type of surgery performed on the spine encompasses operations for trauma, deformity, and myelopathy. The complexity of procedures is continuing to increase and older patients with significant co-morbidities are being offered ever more major procedures for which they would have previously not been considered. Developing areas include surgery for degenerative scoliosis and an increase in operations performed on the anterior lumbar spine Spinal anaesthesia for Lumbar Interverterbral Disc Prolapse (PLID) surgery is becoming increasingly more popular because this anaesthetic technique allows the patient to comfortable self-position and avoid neurological injury that may occur with prone positioning under general anaesthesia. PLID surgery is also a comparatively cost effective surgical procedure. Aim of the study: The aim of the study was to observe the extent of surgical options as per pathological outcome in terms of postoperative pain, immediate functional recovery and patient’s satisfaction for undergoing PLID surgery under spinal anaesthesia. Methods: This observation study was conducted in the department of Neuro surgery Sylhet MAG Osmani Medical College Hospital in association with Central Hospital Limited Sylhet from January 2007 to July 2019. A total of 4000 healthy cooperative patients with ASA I-III grading, undergoing Lumbar Interverterbral Disc Prolapse (PLID) surgery at single level to two levels also recurrent cases operative maximum twice previously were selected as study population. A comprehensive perioperative was carried out documenting per operative events anaesthetic complications, pace of physiological and functional recovery and patient’s satisfaction. Variables were recorded as pain level using a visual analogue scale (VAS) at 1, 6, 12 & 24 hours; patients level of satisfaction during the stay on the ward using verbal rating scale (VER); during of surgery; per amount of blood loss. Data were analyzed by SPSS version 19.0. Results: Among 4000 participants, man was 2416(60.4%) and female 1684 (39.6%). In incidence of PLID surgery 36-45 years age group was almost fifty percent 49.42%. In level of PLID L3/4 was highest 39.0%. Regarding of per operative blood, new was 3337(84.18%) & mean value was 47.65(±9.14) and recurrent 633(15.82%) & mean value was 55.60(±13.80). In duration of surgery the mean of new was 22.51(±3.67)& recurrent 26.72(±5.78). Regarding per operative complications, hypertension was highest 1440(36.0%) followed by hypotension 992(24.4%) & nausea/vomiting 960(24.0%).Average hospital stay was 36 to 48 hours. Conclusion:As our results correspond to the others available studies it is clear that, spinal anaethesia can be definitely used for doing at least 2 levels of PLID surgery as it is also more cost effective and patient need to stay minimum in time duration. Bang. J Neurosurgery 2022; 11(2): 75-79